Skin Lesions in Swine with Decompression Sickness: Clinical Appearance and Pathogenesis - Qing, Long; Ariyadewa, Dinesh K.; Yi, Hongjie; Wang, Yewei; Zhou, Quan; Xu, Weigang (Frontiers in Physiology, 2017)
Skin lesions are visual clinical manifestations of decompression sickness (DCS). Comprehensive knowledge of skin lesions would give simple but strong clinical evidence to help diagnose DCS. The aim of this study was to systematically depict skin lesions and explore their pathophysiological basis in a swine DCS model. Thirteen Bama swine underwent simulated diving in a hyperbaric animal chamber with the profile of 40 msw-35 min exposure, followed by decompression in 11 min. After decompression, chronological changes in the appearance of skin lesions, skin ultrasound, temperature, tissue nitric oxide (NO) levels and histopathology were studied. Meanwhile bubbles and central nervous system (CNS) function were monitored. All animals developed skin lesions and two died abruptly possibly due to cardiopulmonary failure. A staging approach was developed to divide the appearance into six consecutive stages, which could help diagnosing the progress of skin lesions. Bubbles were only seen in right but not left heart chambers. There were strong correlations between bubble load, lesion area, latency to lesion appearance and existence of cutaneous lesions (P=0.007, P=0.002, P=0.004, respectively). Even though local skin temperature did not change significantly, skin thickness increased, NO elevated and histological changes were observed. Increased vessel echo-reflectors in lesion areas were detected ultrasonically. No CNS dysfunction was detected by treadmill walking and evoked potential. The present results suggest skin lesions mainly result from local bubbles and not CNS injuries or arterial bubbles.